2020
DOI: 10.1371/journal.pone.0240828
|View full text |Cite
|
Sign up to set email alerts
|

Using social media influencers to increase knowledge and positive attitudes toward the flu vaccine

Abstract: Seasonal influenza affects millions of people across the United States each year. African Americans and Hispanics have significantly lower vaccination rates, and large-scale campaigns have had difficulty increasing vaccination among these two groups. This study assessed the feasibility of delivering a flu vaccination promotion campaign using influencers, and examined shifts in social norms regarding flu vaccine acceptability after a social media micro influencer campaign. Influencers were asked to choose from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 28 publications
(33 reference statements)
3
98
0
1
Order By: Relevance
“… 40 Enlisting social media influencers and celebrities to promote vaccination may also help uptake. 41 It should be noted that this should be used with a degree of caution. When testing was scarce for average Americans, celebrities were criticized for seemingly being preferentially treated in getting access to tests.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Enlisting social media influencers and celebrities to promote vaccination may also help uptake. 41 It should be noted that this should be used with a degree of caution. When testing was scarce for average Americans, celebrities were criticized for seemingly being preferentially treated in getting access to tests.…”
Section: Discussionmentioning
confidence: 99%
“…In this intervention, the research team recruited micro-influencers, individuals with between 5000–10,000 social media followers, to use researcher-created flu vaccine vetted facts and created vaccine-related posts, videos, or image-based messages on Facebook, Instagram, and Twitter [ 33 ]. Individuals exposed to the intervention reported increased knowledge, positive attitudes about the flu vaccine, subjective norms to vaccinate, and increased flu vaccine uptake [ 33 ]. Future research should use a similar approach of recruiting micro-influencers to increase HPV vaccine uptake and completion among college students.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those of other social campaigns promoted, such as a big campaign conducted in the USA to inform about flu vaccination using influencers and a social media influencer marketing campaign about children’s food intake. The studies reporting on this campaign proved the positive of social media influencers on health promotion [ 16 , 17 ]. Moreover, a UK Survey conducted to investigate health care professional opinions on social media demonstrated that a percentage of 73.3% of responders considered social media as a negative instrument of communication [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as in our study, previous researchers demonstrate the role of medical social influencers in terms of the number of likes, comments, and especially shares of contents [ 28 ]. In the USA, social campaigns on flu vaccination and alimentation using influencers highlighted the positive role of social media influencers for health promotion about children’s food intake [ 16 , 17 ]. Moreover, sharing information as a form of engagement, which enables users to link the medical social influencer post to their social group have been help increasing trust and disseminate health-related information more widely and rapidly [ 29 ].…”
Section: Discussionmentioning
confidence: 99%